(untitled) - Boyle, Charles (Totowa, N.J., 1984)
This book introduce perspectives on science, technology and society. Key issues in advanced industrial society. Questions of control.
Keywords: Công nghệ,Technology; Khía cạnh xã hội,Social aspects